Analisis Hubungan Digital Attitude and Literacy dengan 21st-Century Competencies Siswa SMA di Provinsi Jambi - Fuja Novitra; Festiyed Festiyed; Yohandri Yohandri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This study aims to analyze the correlation between digital attitude and literacy of students with their 21st-century competencies. This research is a quantitative study with a correlation research design. Sample of 156 students from 5 schools in Jambi province. This research method is correlation analysis, data is obtained from questionnaires answered by respondents. The results showed that digital literacy of students has a significant and positive correlation with their 21st-century competencies with significance 0,000. Thus, it was concluded that 21st century competencies was developed along with the development of digital literacy for the development of students’ 21st-century skills, and to realize learning under the demands of 21st-century learning.